Acute respiratory viral infections in monkeys - Dmitry I. Dogadov; Karen K. Kyuregyan; Albert A. Minosyan; Aleksandra M. Goncharenko; Elena V. Shmat; Mikhail I. Mikhailov (Вопросы вирусологии, 2025)
Acute respiratory viral infections (ARVI) are one of the most significant infections affecting the breeding of monkeys, especially among imported and captive primates. Respiratory diseases are also an important cause of morbidity and mortality in wild populations, and most of these infections can affect humans. Many anthropoid species, including apes, are susceptible to ARVI. Outbreaks of spontaneous respiratory infections have been described in many zoos and primatological centers around the world. Moreover, the study of spontaneous and experimental infection in laboratory primates provides an invaluable source of information on the biology and pathogenesis of ARVI and remains an indispensable tool for testing vaccines and drugs. The aim of this literature review was to summarize and analyze published data on the circulation of ARVI causative agents (parainfluenza viruses, adenoviruses, respiratory syncytial virus, influenza viruses, rhinoviruses, coronaviruses, metapneumoviruses, bocaviruses) among wild and captive primates, as well as the results of experimental modeling these infections in monkeys.